EFFECTIVENESS OF TELEREHABILITATION IN PATIENTS WITH OSTEOARTHRITIS OF THE KNEE: A SYSTEMATIC REVIEW - Dr. Kinjal S. Patel; Dr. Daxa G. Mishra (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Osteoarthritis (OA) of the knee leads to pain, restricted mobility, and reduced quality of life. Traditional physiotherapy is effective but often inaccessible due to geographical and logistical constraints. This systematic review assesses the efficacy of telerehabilitation in managing OA knee. A PRISMA-guided search was conducted across PubMed, PEDro, Google Scholar, and ResearchGate using keywords including “Osteoarthritis of knee,” “Telerehabilitation,” and “Exercises in OA knee.” Out of 220 identified studies, 6 met the inclusion criteria. These randomized controlled trials (RCTs) involved 331 participants and implemented various telerehabilitation strategies, such as mobile apps and video conferencing. Findings reveal telerehabilitation is as effective as conventional physiotherapy in improving pain, function, flexibility, and quality of life. It offers added benefits of cost-efficiency, convenience, and increased accessibility. The results support telerehabilitation as a viable and effective alternative or adjunct to in-person therapy for OA knee management.